Update Breast Cancer 2021 Part 4 – Prevention and Early Stages - Thomssen, Christoph; Fehm, Tanja N.; Stickeler, Elmar; Fasching, Peter A.; Janni, Wolfgang; Kolberg-Liedtke, Cornelia; Kolberg, Hans-Christian; Lüftner, Diana; Müller, Volkmar; Schütz, Florian; Belleville, Erik; Bader, Simon; Untch, Michael; Welslau, Manfred; Thill, Marc; Hartkopf, Andreas D.; Tesch, Hans; Ditsch, Nina; Lux, Michael P.; Wöckel, Achim; Aktas, Bahriye; Schneeweiss, Andreas; Würstlein, Rachel (Geburtshilfe und Frauenheilkunde, 2022)
This past year has seen new and effective options for further improving treatment outcome in many patients with early-stage breast cancer. Patients with hormone receptor-positive disease benefited significantly from the addition of the CDK4/6 inhibitor abemaciclib to endocrine adjuvant therapy. In triple-negative disease, data were presented for two treatment regimens. Patients with advanced disease (stage 2 and 3) benefit from neoadjuvant treatment with the immune checkpoint inhibitor pembrolizumab in combination with standard chemotherapy, regardless of PD-L1 expression. When neoadjuvant therapy has failed to achieve the desired remission in BRCA1 and BRCA2 mutations, the administration of the PARP inhibitor olaparib has demonstrated an impressive response. Other data address translational issues in HER2-positive breast cancer and neoadjuvant therapy approaches with the oral SERD giredestrant and the PARP inhibitor talazoparib. This review presents and analyses the findings of this yearʼ s most important study outcomes.Im vergangenen Jahr wurden für viele Patientinnen mit Mammakarzinom in frühem Krankheitsstadium neue und effektive Optionen für eine weitere Verbesserung der Behandlungsergebnisse gezeigt. Für Patientinnen mit hormonrezeptorpositiver Erkrankung zeigte sich ein signifikanter Zusatzeffekt durch den Einsatz des CDK4/6-Inhibitors Abemaciclib zusätzlich zur endokrinen adjuvanten Therapie. Bei triple-negativer Erkrankung wurden Daten für 2 Therapieprinzipien gezeigt. Patientinnen mit fortgeschrittener Erkrankung (Stadium 2 und 3) profitieren von dem neoadjuvanten Einsatz des Immuncheckpoint-Inhibitors Pembrolizumab unabhängig von der PD-L1-Expression in Kombination mit einer Standardchemotherapie. Bei BRCA1- oder BRCA2-Mutation wurde ein eindrucksvoller Benefit durch den Einsatz des PARP-Inhibitors Olaparib gezeigt, wenn die neoadjuvante Therapie nicht zur gewünschten Remission geführt hat. Weitere Daten betreffen translationale Fragestellungen beim HER2-positiven Mammakarzinom sowie neoadjuvante Therapieansätze mit dem oralen SERD Giredestrant und dem PARP-Inhibitor Talazoparib. In dieser Übersichtsarbeit werden die Ergebnisse der wichtigsten Studienergebnisse dieses Jahres vorgestellt und bewertet.
Keywords: BRCA (breast cancer associated gene); breast; genetics; Her-2/neu (human epidermal growth factor receptor); hormonal receptor; breast cancer